2000
DOI: 10.1007/s002590050560
|View full text |Cite
|
Sign up to set email alerts
|

Sternal wound infection revisited

Abstract: Sternal wound infections (SWIs) can be subdivided into two types, superficial or deep, that require different treatments. The clinical diagnosis of superficial SWI is normally easy to perform, whereas the involvement of deep tissues is frequently difficult to detect. Therefore, there is a need for an imaging study that permits the assessment of SWIs and is able to distinguish between superficial and deep SWI. The present work was a prospective study aiming to evaluate the role of technetium-99m hexamethylpropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Scintigraphy can however be useful in the diagnosis of sternal fractures during the early period after thorax trauma (Erhan et al) or for diagnosis of deep sternal infections after sternotomy for cardiac illnesses (Liberatore et al). [16][17][18] We stress the importance of excluding any life-threatening diseases first, before diagnosing a patient with xiphodynia.…”
Section: Discussionmentioning
confidence: 99%
“…Scintigraphy can however be useful in the diagnosis of sternal fractures during the early period after thorax trauma (Erhan et al) or for diagnosis of deep sternal infections after sternotomy for cardiac illnesses (Liberatore et al). [16][17][18] We stress the importance of excluding any life-threatening diseases first, before diagnosing a patient with xiphodynia.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear medicine studies with Tc-99 m HMPAO-labelled leukocytes [ 133 , 135 , 136 , 137 , 138 , 139 , 140 ], Ga-67 [ 134 , 137 , 141 ], indium 111-WBC [ 128 , 138 , 139 ], combined Tc-99 MDP and In-111 WBC [ 132 , 142 , 143 ] (combined Tc-99 MDP and In-111 WBC [ 144 ], 99mtc-labeled monoclonal granulocyte antibody scintigraphy [ 145 ] and, more recently, 99m Tc-UBI 29-41 [ 146 ], have been used in the study of post-sternotomy infection and post-sternotomy osteomyelitis [ 126 , 127 , 131 , 133 , 144 ]. Rouzet et al [ 135 ] showed the usefulness of serial studies with planar scintigraphy in cases of suspected PSM relapse.…”
Section: Diagnosismentioning
confidence: 99%
“…CT may provide better depiction of features such as bone erosion, periosteal reaction, sharply demarcated areas of sclerosis, and soft-tissue swelling (Fig 13) (53,54). When the CT appearance is nonspecific, nuclear medicine studies with radiolabeled leukocytes may provide additional information (54,55).…”
Section: Infectious Processes Primary and Secondary Osteomyelitismentioning
confidence: 99%